Digital Transformation of Human Resource Management in Enhancing the Competitive Advantage of the Tourism Sector in Riau - Iskandar; Risman; Defi Warman; Rizqi Fakhri; Fatkhurahman (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the role of Digital Human Resource Management (Digital HRM) in supporting the achievement of competitive advantage within tourism organizations. Design/methodology/approach – A quantitative explanatory approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 150 employees, supervisors, and HR managers in tourism-related organizations in Riau, Indonesia, using purposive sampling. Findings – The findings indicate that Digital HRM is positively related to the development of HR capabilities and organizational competitiveness. In addition, HR capabilities contribute to competitive advantage and serve as a partial mediator in the relationship between Digital HRM and competitive advantage. These results indicate a dual-path mechanism, where Digital HRM contributes both indirectly through capability development and directly through enhanced organizational efficiency. Research limitations/implications – The study is limited by its cross-sectional design, self-reported data, and regional scope. The findings extend the Resource-Based View by highlighting the complementary role of digital systems and human capabilities. Practical implications – Tourism organizations need to combine the use of digital HR systems with ongoing employee development programs in order to maintain their competitive position. Originality/value – This study provides context-specific evidence and clarifies how Digital HRM drives competitive advantage through both direct and mediated pathways.